ETCH PIT FORMATION ON IRON SILICATE SURFACES DURING SIDEROPHORE-PROMOTED DISSOLUTION - Buss H.L.; Lüttge A.; Brantley S.L. (My University, 2007)
Understanding the effects of microbiota on mineral alteration requires the ability to recognize evidence of bacteria-promoted dissolution on mineral surfaces. Although siderophores are known to promote mineral dissolution, their effects on mineral surfaces are not well known. We have utilized atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and Mirau vertical scanning interferometry (VSI) to investigate surfaces after incubation with the siderophore desferrioxamine-B mesylate (DFAM) and under colonies of bacteria. Iron-silicate glass planchets chemically similar to hornblende were incubated in buffered growth medium with siderophore-producing bacteria (Bacillus sp.) for 46 days with parallel abiotic experiments conducted with and without 240 μM DFAM, with and without 0.01 g l- 1 of microbially produced extracellular polysaccharides (EPS, alginate or xanthan gum). Some glass planchets were protected by dialysis tubing from direct contact with the EPS. Weekly sampling and analysis of all filtered sample solutions showed negligible Fe and Al release in the control experiments and significant release of Fe and Al in the presence of DFAM, with negligible changes in pH. Concentration of Fe in the filtered solutions after incubation with bacteria was below detection, consistent with uptake of Fe by cells. Release of Fe, Al, and Si in control, xanthan-only, and alginate-only experiments was negligible. Release of these elements was enhanced in all experiments containing DFAM, and greatest in alginate + DFAM experiments. AFM and VSI analyses reveal widespread, small etch pits and greater root mean squared roughness on siderophore-exposed surfaces and fewer, localized, larger etch pits on bacteria-exposed surfaces. This is the first documented case of etch pit development during siderophore-promoted dissolution. Roughness was not affected by the growth medium, alginate, or xanthan gum alone. The roughness trends among samples correlate with trends in Fe depletion documented by XPS. Enhanced dissolution and roughness cannot be attributed to direct contact with EPS because no significant chemical or physical differences were observed between surfaces directly exposed to EPS and those protected by dialysis tubing. Acetate released from the EPS may have enhanced the siderophore-promoted dissolution. Siderophores produced by Bacillus sp. may be responsible for some of the 'biopits.' The difference in size and distribution of the biopits may be related to colonization. © 2007 Elsevier B.V. All rights reserved.
Keywords: BIOFILMS; DESFERRIOXAMINE; ETCH PITS; HORNBLENDE; SIDEROPHORES